Strategi Guru Pendidikan Agama Islam dalam Membina Akhlak Siswa Di SMP - Sya'roni, Mohd (Center for Religious Studies and Social Empowerment Foundation, 2022)
This article examines the strategy of Islamic religious education teachers in fostering student morals at SMP Negeri 7 Danau Kerinci District, Kerinci Regency. Based on the grandtour, it was found that there were several problems related to the moral development of students, including; lack of student attention during teaching and learning takes place, low student discipline, and lack of student etiquette. The focus of this research is how do teachers apply their strategies in fostering students' morals in learning Islamic education? This research is a qualitative research with the determination of research subjects using the purposive side technique. This study found that the strategies of Islamic religious education teachers in fostering student morals at SMP Negeri 7 Kerinci include; (a) habituation, which includes first getting students to read prayers and short letters before starting KBM, getting students to pray dzuhur in congregation, and getting students used to keeping the school environment clean, (b) exemplary, which includes, the teacher comes on time, the teacher says greetings and shaking hands when meeting teachers and students, teachers dress neatly and politely, and teachers always accompany students in every activity, (c) advice, which includes teachers giving advice in the KBM process, and giving advice in the form of reprimands and punishments. Artikel ini mengkaji tentang strategi guru pendidikan Agama Islam dalam membina akhlak siswa di SMP Negeri 7 Kecamatan Danau Kerinci Kabupaten Kerinci. Berdasarkan grandtour, ditemukan adanya beberapa permasalahan terkait pembinaan akhlak siswa antara lain; kurangnya perhatian siswa saat KBM berlangsung, rendahnya kedisiplinan siswa, dan kurangnya adab siswa. Fokus penelitian ini adalah bagaimana guru menerapkan strateginya di dalam membina akhlak siswa dalam pembelajaran pendidikan Agama Islam? Penelitian ini merupakan penelitian kualitatif dengan penentuan subjek penelitian menggunakan teknik purposive side. Penelitian ini menemukan bahwa strategi guru pendidikan agama Islam dalam membina akhlak siswa di SMP Negeri 7 Kerinci antara lain; (a) pembiasaan, yang meliputi pertama membiasakan siswa membaca doa dan surat-surat pendek sebelum memulai KBM, membiasakan siswa shalat dzuhur berjamaah, dan mebiasakan siswa menjaga kebersihan lingkungan sekolah, (b) keteladanan, yang meliputi, guru datang tepat waktu, guru mengucap salam dan berjabat tangan saat bertemu guru maupun siswa, guru berpakaian rapi dan sopan, dan guru senantiasa mendampingi siswa dalam setiap kegiatan, (c) nasehat, yang meliputi guru memberikan nasehat dalam proses KBM, dan memberikan nasehat berupa teguran dan hukuman.